2018
DOI: 10.3389/fphys.2018.01481
|View full text |Cite|
|
Sign up to set email alerts
|

Leg Press vs. Smith Machine: Quadriceps Activation and Overall Perceived Effort Profiles

Abstract: First aim was describing Smith machine squat and leg press exercise as nominal load, knee extensors activity, and rating of perceived exertion. Second aim was developing predictive equations to provide same muscular activation and same perceived exertion nominal loads during the two exercises. To do that, vastus lateralis and vastus medialis activation, as their summed surface electromyography signal integrals, and overall perceived exertions were measured at different nominal loads during Smith machine squat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Furthermore, immediately after the walking exercise, the participant was asked to express their perception of fatigue as a value based on the Borg scale (0 < 20). On a different day, each participant was assessed with regard to their maximal repetitions during the leg-press exercise (Padulo et al, 2017;Migliaccio et al, 2018) and the 1-RM based on the Brzycki method was calculated at the same time (Padulo et al, 2015). To ensure standardization of the procedure the following method was used.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, immediately after the walking exercise, the participant was asked to express their perception of fatigue as a value based on the Borg scale (0 < 20). On a different day, each participant was assessed with regard to their maximal repetitions during the leg-press exercise (Padulo et al, 2017;Migliaccio et al, 2018) and the 1-RM based on the Brzycki method was calculated at the same time (Padulo et al, 2015). To ensure standardization of the procedure the following method was used.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a significant relationship was observed between the RPE and SFI. These results indicated that RPE could be used as an exercise fatigue predictor, which makes sense because RPE integrates more physiological-related information induced by resistance exercises [ 18 , 34 ]. Conventionally, RPE is measured upon completion of required sets and/or sessions, as represents of subjective feelings of discomfort overall [ 25 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between RPE, velocity loss, and SFI during exercise was examined using Spearman’s correlation analysis. The non-overlapping part of the three conditions was used in the correlation analysis [ 28 , 34 ]. Statistical significance was acceptable at p < 0.05 in all analyses.…”
Section: Methodsmentioning
confidence: 99%
“…A linear encoder (Ergotest Innovation AS R , Linear displacement sensor SKU 1260 MuscleLAb System, Norway) connected to an integrated data analysis system was used (Ergotest Innovation AS R , MuscleLAb System, Norway). The speed was used to calculate mean and maximum power using the Musclab R as described previously (Padulo et al, 2015a(Padulo et al, , 2017Migliaccio et al, 2018;Santos et al, 2018).…”
Section: Design and Proceduresmentioning
confidence: 99%